ChemInform Abstract: Oxidative Coupling of Organoboron Compounds. Issue 36 (9th September 2014) - Dhital, Raghu Nath; Sakurai, Hidehiro
Abstract Review: [summary on both the seminal early work and recent developments in the area of transition‐metal‐catalyzed oxidative homocoupling reactions of organoboron compounds and mechanistic details; 71 refs.